Filosof Islam Pertama (Al-Kindi) - Muhammad Asrul Pattimahu MA (Budapest International Research and Critics University, 2017)
This research aims to analyze the first Islamic philosophers (Al-Kindi). Philosophy which developed in the Islamic world is a legacy of Greek philosophy. Many Muslim philosophers took the thoughts of Aristotle, Plato, and Plotinus, so many Greek philosophical theories were taken by Muslim philosophers. It is this influence of Greek philosophy which is the basis of the counter-expression around the problem of philosophy in Islam. The results showed that the birth and development of philosophical thought in Islam was a necessary historical reality because of the interaction that was built between Muslim Arabs with conquered areas (non-Muslim nations), namely the Persians, Indians and especially Greek people. , so Islamic philosophy is said to contain many elements of Hellenism.